Labour shortage in the plantation industry myths and realities. - Nayagam, James
Based on the RRIM survey and other studies carried out in the recent past it could be concluded that spme plantations in certain regions of the country are experiencing labour shortage. However,taking the plantation industry as a whole the shortage at the present moment which amounts to less than five percent is not a very serious one. Since the flow of young workers from the agricultural sector to the industrial sector is a normal process of economic development,as industrialization in Malaysia accelerates the rural-urban migration will increase. Thus,labour shortage in the plantations is likely to grow in magnitude over time. The permanent solution to this problem is through the innovation of labour saving technioques for filed maintenance and harvesting and processing of the crops.